O controle interno como ferramenta para o aprimoramento da gestão no Estado de Minas Gerais - Oliveira, Carlos Humberto Ornelas (2025)
In a society where the themes of efficiency, effectiveness, and transparency in public management are prominent, studying internal control and its implications becomes fundamental, as internal control practices can function as tools for improving public management. However, these practices may prove ineffective when based on isomorphisms, myths, and ceremonies, giving an appearance of modernity and compliance to governmental processes when, in fact, they are ineffective. The aim of this study is to assess the relevance of internal control practices for management efficiency. To this end, a qualitative, exploratory research was conducted, using documental analysis and semi-structured interviews with managers and auditors. Thirtyone reports and sixty audit notes from the period between 2019 and 2024 were analyzed, focusing on the Secretariats of Social Development, Education, and Health of the State of Minas Gerais. Additionally, seven auditors and six high-ranking public administration officials from these departments were interviewed. The main findings revealed the presence of normative isomorphism, such as the institutionalized use of manuals from other organizations in the field of control, like the CGU and TCU, as well as the use of the E-aud computerized system. Institutional myths were also observed, such as the adoption of the IIA's Three Lines model, and ceremonial practices, such as the issuance of reports and audit notes after the implementation of corrective measures in the work processes. Therefore, this research contributes to a better understanding of how isomorphism, myths, and ceremonies can influence internal control activities, offering a critical analysis of the impact of these factors on control practices.